Analisis Kesulitan Belajar Membaca Permulaan Siswa Kelas II Pada Mata Pelajaran Bahasa Indonesia di Madrasah Ibtidaiyah Pesantren Ummushabri Kendari - T, Hikmawati; Ishaq, Nurul Istiqamah; Rifki, Faisal; Arif, Tarman A (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2025)
This study aims to analyze beginning reading difficulties among second-grade students at MI Pesantren Ummushabri Kendari. The research used a qualitative descriptive method with data collected through observation, interviews, and documentation. The findings reveal that students struggle with: (1) decoding letters into syllables, (2) combining syllables into words, and (3) distinguishing visually similar letters such as b-d and p-q. Contributing factors include physical conditions, intelligence level, and lack of family support. The study highlights the essential roles of teachers and parents in supporting early reading development to help minimize learning barriers.